From research on the scriptorium of the Cistercian monastery in Mogiła until the beginning of the 16th century - Domżał, Zbigniew; Wałkówski, Andrzej (Interdyscyplinarium nauk o mediach i kulturze, 2020)
The scriptorium of the Cistercian monastery in Mogila should be considered as the best developed, especially in reference to the 13th century. It has three coverages in a book form and numerous articles. The period up to the end of the 13th century is relatively best developed. It was established that at the time 29 documents were created in the scriptorium: The Polish-Silesian Chronicle and The Nocturnale Cantuale codex, which did not survive and we know about it from the later made (16th century) monasterial chronicles of Nicholas from Cracow. Three monastic writers known by the name were indicated: abbot Herman, brother Ludwik and abbot Engelbert. In addition, 21 anonymous monastic writers who wrote down monastery documents were disclosed. There are clear similarities in the writing habits of the Cistercian monastery in Mogila to the scriptorium of its matrix in Lubianka, especially in the twenties and thirties of the 13th century and their subsequent disappearance was the result of the emergence of a new generation of monastic writers. The continuation of the research covered the period from the 14th to the beginning of the 16th century. From that time, 186 documents concerning the Cistercian monastery in Mogila and 29 codices were preserved. During the research it was established that the following Cistercians could have worked in the scriptorium: Jan Wartenberg (1375/78–1389), Arnold (1412), Nicholas Brygier (1426–1438), doctor Jacob from Paradyz (1420–1441), brother N (1441), later abbot Peter Hirszberg (1447), brothers George from Sambor and Nicholas (1461–1475), brother Nicholas from Cracow, for example author of the monastery chronicle (1452–1505/6).